Fungi composition in settled dust associated with fractional exhaled nitric oxide in school children with asthma - Mohd Isa, Khairul Nizam; Jalaludin, Juliana; Hashim, Zailina; Thian, Leslie Lung Than; Hashim, Jamal Hisham; Norback, Dan (Elsevier BV, 2022)
Fungi exposure has been significantly linked to respiratory illness. However, numerous fungi taxa that are potentially allergenic still undocumented and leave a barrier to establishing a clear connection between exposure and health risks. This study aimed to evaluate the association of fungi composition in settled dust with fractional exhaled nitric oxide (FeNO) levels among school children with doctor-diagnosed asthma. A cross-sectional study was undertaken among secondary school students in eight schools in the urban area of Hulu Langat, Selangor, Malaysia. A total of 470 school children (aged 14 years old) were randomly selected and their FeNO levels were measured and allergic skin prick tests were conducted. The settled dust samples were collected and analysed by using metagenomic technique to determine the fungi composition. The general linear regression with complex sampling was employed to determine the interrelationship. In total, 2645 fungal operational taxonomic units (OTUs) were characterised from the sequencing process which belongs to Ascomycota (60.7 %), Basidiomycota (36.4 %), Glomeromycota (2.9 %) and Chytridiomycota (0.04 %). The top five mostly abundance in all dust samples were Aspergillus clavatus (27.2 %), followed by Hyphoderma multicystidium (12.2 %), Verrucoconiothyrium prosopidis (9.4 %), Ganoderma tuberculosum (9.2 %), and Heterochaete shearii (7.2 %). The regression results indicated that A. clavatus, Brycekendrickomyces acaciae, Candida parapsilosis, Hazslinszkyomyces aloes, H. multicystidium, H. shearii, Starmerella meliponinorum, V. prosopidis were associated in increased of FeNO levels among the asthmatic group at 0.992 ppb (95 % CI = 0.34–1.68), 2.887 ppb (95 % CI = 2.09–3.76), 0.809 ppb (95 % CI = 0.14–1.49), 0.647 ppb (95 % CI = 0.36–0.94), 1.442 ppb (95 % CI = 0.29–2.61), 1.757 ppb (95 % CI = 0.59–2.87), 1.092 ppb (95 % CI = 0.43–1.75) and 1.088 ppb (95 % CI = 0.51–1.62), respectively. To our knowledge, this is a new finding. The findings pointed out that metagenomics profiling of fungi could enhance our understanding of a complex interrelation between rare and unculturable fungi with airway inflammation.